2000
DOI: 10.1007/bf02484288
|View full text |Cite
|
Sign up to set email alerts
|

High-grade adenoid cystic carcinoma originating from the lacrimal gland

Abstract: Among primary lacrimal gland tumors, adenoid cystic carcinoma (ACC) is the most common malignant epithelial neoplasm; it is characterized by local intracranial invasion. A case with unusual dumbbell-type intracranial extension representing cavernous sinus syndrome is described. A 49-year-old woman was admitted to our hospital with right cavernous sinus syndrome. Computerized tomographic (CT) scans and magnetic resonance (MR) imaging demonstrated well-enhanced intraorbital and middle fossa tumors mimicking mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 15 publications
0
32
0
5
Order By: Relevance
“…[1][2][3]6) In addition, three routes have been reported for the intracranial invasion of salivary gland ACCs: the eustachian tube (in the peritubal space), 1,[5][6][7] the mandibular and maxillary nerves, and the internal carotid artery. 3,5) In the present case, the tumor was located in the right Meckel's cave and cavernous sinus with invasion of the foramen rotundum, foramen ovale, and superior orbital fissure. These findings suggested that the intracranial invasion occurred through perineural infiltration along the mandibular or maxillary nerves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3]6) In addition, three routes have been reported for the intracranial invasion of salivary gland ACCs: the eustachian tube (in the peritubal space), 1,[5][6][7] the mandibular and maxillary nerves, and the internal carotid artery. 3,5) In the present case, the tumor was located in the right Meckel's cave and cavernous sinus with invasion of the foramen rotundum, foramen ovale, and superior orbital fissure. These findings suggested that the intracranial invasion occurred through perineural infiltration along the mandibular or maxillary nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Two major regions of intracranial invasion are the optic chiasm and the gasserian ganglion. 5,6) We report a case of ACC that mimicked a trigeminal schwannoma on neuroimaging. The diagnosis was established by histological examination, but no evidence of a primary lesion was detected, which is very unusual.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 A maioria dos CAC origina-se das glândulas salivares maiores e menores, nasofaringe e glându-las lacrimais. 4,6 É reconhecido pelo seu crescimento lento, padrão de recorrência e metástases a distância.…”
Section: Introductionunclassified